From the House to the Streets : The Cuban Woman's Movement for Legal Reform, 1898-1940 - Stoner, K. Lynn (Book collections on Project MUSE., 1991)
If you want to find out what a rock critic, a syndicated columnist, and scholars of American literature have to say about one of America's most important contemporary novelists, turn to Introducing Don DeLillo. Placing the author's work in a cultural context, this is the first book-length collection on DeLillo, adding considerably to the emerging critical discourse on his work. Diversity is the key to this striking assemblage of cultural criticism edited by Frank Lentricchia. Special features include an expanded version of the Rolling Stone interview with the author ("An Outsider in this Societ